Design and Performance Analysis of Low Sub-threshold Swing p-Channel Cylindrical Thin-film Transistors - Akkili, Viswanath G.; Srivastava, Viranjay M. (Micro and Nanosystems, 2023)
Background: Tin monoxide (SnO) attracts considerable interest for p-channel Cylindrical Thin Film Transistors (CTFTs) applications due to their merits, including low hole effective mass, Sn s and O p orbital hybridization at the valance band maxima, and ambipolar nature, among other p-type oxide semiconductors. Objective: This article analyses the influence of channel radius and the impact of dielectric materials on the performance of SnO-based CTFT devices through 3D numerical simulations. Methods: The radius of the active layer in the CTFT was varied in the range from 10 nm to 30 nm, and it has been observed that an increase in channel radius reduces the switching behavior of the devices. Results: The 10 nm thick CTFT exhibited superior results with a lower threshold voltage of 1.5 V and higher field-effect mobility of 13.12 cm2/V-s over other simulated CTFTs. Conclusion: The obtained mobility values are superior to the existing planar TFTs reports. To improve the device performance further, the CTFTs with various dielectric materials have been simulated and optimized with high field-effect mobility and low sub-threshold swing values.
Keywords: dielectrics